ECONOMIC VALUATION OF MANGROVE ECOTOURISM IN BELAWAN SICANANG - Fines Indah Sari; Lamun Bathara; Trisla Warningsih (Berkala Perikanan Terubuk, 2021)
Belawan Sicanang Village is a sub-district that still has a mangrove forest ecosystem in the city of Medanwith a mangrove area of about 470 ha is divided into the fisheries an area 466 ha and ecotourism sectorswith an area of 4 ha. This research was conducted in Belawan Sicanang Village, Medan Belawan District,North Sumatra, Indonesian in 05 January – 05 February 2021. This study aims to measure the amount ofeconomic value obtained by Mangrove Ecotourism in Belawan Sicanang Village seen from consmersurplus with individual travel cost. Method respondents were determined using accidental samplingmethod with a total of 40 respondents. The result of the study concluded that in calculating the economicvalue of Belawan Sicanang Mangrove Ecotourism using the travel cost method with a consumer surplusvalue (CS), it was obtained IDR 412,169 per year and the economic value seen from the travel costmethod was IDR 1,648,159,472 per year.